Remote ischaemic preconditioning does not protect the heart in patients undergoing coronary artery bypass grafting - Lomivorotov, Vladimir V. (Oxford University Press, 2012)
Remote ischaemic preconditioning (RIPC) gained attention as a possibility to reduce myocardial injury after a subsequent sustained episode of myocardial ischaemia. This prospective randomized study was carried out to assess whether RIPC reduces myocardial injury in coronary artery bypass grafting patients. Eighty patients were assigned to remote preconditioning or control treatment. Ischaemic preconditioning was induced by three 5-min cycles of upper limb ischaemia and reperfusion after anaesthesia induction. Haemodynamic and markers of myocardial damage were analysed preoperatively and over 48 h postoperatively. The cardiac index was higher immediately after remote preconditioning in the main group. There were no differences in other haemodynamic, troponin I and creatine kinase-MB concentrations at any time point between groups. Thus, short-term remote preconditioning improves haemodynamics and does not reduce myocardial injury after coronary artery bypass surgery. Further study of high-risk patients may be needed to fully evaluate the clinical effect of RIPC.